Subdural evacuating port system with subdural thrombolysis for the treatment of chronic subdural hematoma in patients older than 80 years - Liu, Tianqing; Gao, Zhenwen; Zhou, Jianjun; Lai, Xiaoyan; Chen, Xiaomei; Rao, Qiong; Guo, Dongbin; Zheng, Jinliang; Lin, Fuxin; Lin, Yuanxiang; Lin, Zhiqin (Frontiers in Neurology, 2023)
Objective: Subdural evacuating port system (SEPS) is a minimally invasive approach that can be performed under local anesthesia for the treatment of chronic subdural hematoma (CSDH). Subdural thrombolysis has been described as an exhaustive drainage strategy and found to be safe and effective for improving drainage. We aim to analyze the effectiveness of SEPS with subdural thrombolysis in patients over 80 years old. Method: Consecutive patients aged ≥80 years old who presented with symptomatic CSDH and underwent SEPS followed by subdural thrombolysis between January 2014 and February 2021 were retrospectively studied. Outcome measures included complications, mortality, recurrence, and modified Rankin Scale (mRS) score at discharge and 3 months. A literature review of burr-hole drainage (BHD) in very elderly patients with CSDH was performed. Results: In total, 52 patients with CSDH in 57 hemispheres were operated on, with a mean age of 83.9 ± 3.3 years and 40 (76.9%) were male. The preexisting medical comorbidities were observed in 39 patients (75.0%). Postoperative complications occurred in 9 patients (17.3%), with 2 having significant complication (3.8%). The complications observed included pneumonia (11.5%), acute epidural hematoma (3.8%), and ischemic stroke (3.8%). One patient experienced contralateral malignant middle cerebral artery infarction and died of subsequent severe herniation, contributing to a perioperative mortality of 1.9%. Discharge and 3 months favorable outcomes (mRS score 0-3) were achieved in 86.5% and 92.3% of the patients, respectively. CSDH recurrence was observed in 5 patients (9.6%) and repeat SEPS were performed. Conclusion: As an exhaustive drainage strategy, SEPS followed with thrombolysis is safe and effective with excellent outcome among elderly patients. It is a technically easy and less invasive procedure with similar complications, mortality, and recurrence rates compared with BHD in the literature.